Effects of Bi2O3–B2O3–ZnO glass additive on structure, ferroelectric and dielectric properties of BiFeO3 ceramics. (25th January 2020) - Bai, Peijia; Zeng, Yiming; Han, Jiao; Wei, Yongxing; Li, Yutong; Li, Mingwei
Abstract: Lead-free BiFeO3 ceramics doped with varying amounts of Bi2 O3 –B2 O3 –ZnO (BBZ) glass, that is, x wt% ( x = 0.0, 0.5, 1.0, 1.5, and 2.0) were prepared via the traditional solid-state reaction route. The effects of BBZ glass content on the phase composition, microstructure, dielectric, and ferroelectric properties of BiFeO3 ceramics were investigated. X-ray diffraction results confirmed that BBZ glass doping increased the formation of secondary phases (Bi2 Fe4 O9 and Bi25 FeO39 ). Scanning electron microscopy images showed that the samples with the addition of BBZ glass showed a heterogeneous size distribution of grains and more porosity. With the increase of the BBZ glass content, the fluctuation of Fe-ions was decreased and the bond strength of the Bi-O was increased. The samples with BBZ glass addition showed smaller dielectric constant and more saturated polarization hysteresis loops compared with pure BiFeO3 . The Curie temperature ( T C ) decreased gradually from 825.8 °C for x = 0.0 to 637.0 °C for x = 2.0. In addition, leakage current density decreased with the addition of BBZ glass. These changes of the electric properties were related to the heterogeneous size distribution of grains, the generation of secondary phases and the increase of the concentration ratios of Fe 3+ and Fe 2+ in BiFeO3 - x BBZ samples.